2019
DOI: 10.4236/pp.2019.1010035
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Evaluation of Poly-γ-Glutamic Acid Hydrogel Mixtures with Basic Drugs or Acidic Drugs: Effect on Ease of Swallowing and Taste Masking

Abstract: The purpose of this study was to prepare a poly-γ-glutamic acid hydrogel (PGA gel), to examine its ease of swallowing using texture profile analysis (TPA) and to evaluate its taste-masking effects on basic or acidic drugs using the artificial taste sensor. Using TPA, 0.5% and 1.0% PGA gels, 0.5% and 1.0% agar and 1.0% ι-carrageenan in the absence of drug was examined the hardness, adhesiveness and cohesiveness, ranked according to permission criteria published by the Japanese Consumers Affairs Agency. 0.5% PGA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…In the food field, γ‐PGA is used as an ingredient to improve the flavour of food. It had been reported that γ‐PGA inhibited both acidic and basic bitterness (Kojima et al ., 2019). Some researchers had found that γ‐PGA improved the quality of surimi and reduced the deterioration of surimi gel during the freezing process (Tao et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In the food field, γ‐PGA is used as an ingredient to improve the flavour of food. It had been reported that γ‐PGA inhibited both acidic and basic bitterness (Kojima et al ., 2019). Some researchers had found that γ‐PGA improved the quality of surimi and reduced the deterioration of surimi gel during the freezing process (Tao et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%